Impact of Reward system on Employee Motivation “A case study of selected Universities in Jalalabad Afghanistan”: https://doi.org/10.5281/zenodo.16895972 - Ashoqullah Karimi; Mujeeb UR Rahman Habib; Mahmood (`, 2025)
Employees are the main factors of success for any organization their fore it is necessary to motivate them with both financial and none financial reward system. This research paper is design to show the relationship between reward system and employee motivation in the selected university of Afghanistan Nangrahar province. In current study reward system is independent variable which is measured through financial and none financial reward, while employee motivation is dependent variable. Mixed research method were adopted and primary data were used by distributed questioner to the respondent for collection of data. The collected data were analysis through SPSS software, for checking the reliability and validity, descriptive statistics, and hypothesis testing. Result Reveal that all the hypothesis are accepted as the value of the created hypothesis are less than 0.05. Furthermore r = 0.364 shoe positive change in between reward system and employee motivation and indicate that one unit increase in reward system will bring 0.364 units change in motivation, for none financial reward r = 0.399 indicate positive change mean that one unit increase in non-financial reward will bring 0.399 units change in employee motivation similarly for financial reward r = 0.414 indicate positive change between financial reward and employee motivation Keywords: Reward System, Financial Reward, None Financial Reward, Employee Motivation